ResponPertumbuhanBibitKakao (Theobroma cacao L.)terhadapKombinasiPupuk NPK denganPupukOrganikCairLimbah Ikan Nila - Arion Hotmartua Sihombing; Tengku Nurhidayah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
1This study aims to determine the best combination of NPK and liquid organic fertilizer from tilapia waste on the growth of cocoa seeds (Theobroma cacao  L.). This research was conducted at Experimental Garden Faculty of Agriculture, University of Riau, Pekanbaru. The study was conducted from April 2019 to August 2019. The study used a completely randomized design (CRD) consisting of seven treatments and three replications. The treatments used were NPK fertilizer 12.48 g/polybag, NPK fertilizer 6.24g/polybag + LOFtilapia fish waste25%, NPK fertilizer 6.24 g/polybag + LOFtilapia fish waste50%, NPK fertilizer 6.24 g/polybag + POC tilapia fish waste75%, NPK fertilizer 12.48 g/polybag + LOF tilapia fish waste25%, NPK fertilizer 12.48 g/polybag + LOFtilapia fish waste50% and NPK fertilizer 12.48 g/polybag + LOF tilapia fish waste75%. The parameters observed were seedling height(cm),numberofleaves(strands),girth(cm),leaflength(cm),width(cm),root volume (ml), root crown ratio (g), weight dry seedlings (g), and leaf area (cm2). The results of the analysis were further tested using multiple range test Duncan'sat the 5% level. The results showed that the combination of NPK fertilizer treatment with LOF tilapia fish waste had an effect on the parameters of seed height, number of leaves wrapped in stems, leaf length, leaf width, root volume, root crown ratio, seed dry weight and leaf area. The application of 6,24 g of NPK fertilizer with 50% LOF tilapia fish waste gave the best growth results for cocoa seedlings in all parameters for cocoa seed growth. Keywords: Cocoa seeds, NPK fertilizer, tilapiawasteliquid organic fertilizer